THE RELATIONSHIP BETWEEN VITALITY AND FLOURISHING IN THE WORKPLACE IN THE INDUSTRY 4.0 - AL-Hadrawi, Baqer Khudair; Rajeh Jawad, Ameer (The journal of contemporary issues in business and government, 2022)
The Industry 4.0 has shown radical changes that impact workers, organizations, and societies in general. Unexpected challenges accompany these changes in cognition, emotion, and behavioral levels. These new challenges put it upon the organizations to address employees’ perceptions and deal with rapid technological innovations and concepts of work and new employment. Therefore, this study aims to test the relationship between vitality and Flourishing in the workplacein light of the Industry 4.0. The paper adopts a descriptive-analytical approach to achieve this goal. Business organizations have created a favorable climate in which entrepreneurs and businessmen can develop their businesses to enable organizations to create new jobs. Assisting industrial and commercial institutions, the labor market, businessmen, and workers to achieve the highest possible development levels and adapt to this progress in the workplace, rather than slowing and disrupting the pace of technological advancement.